Kemampuan berpikir kritis peserta didik materi keberagaman pada pembelajaran pendidikan kewarganegaraan kelas VA sekolah dasar - Yulianti, Eva; Mahfud, Hasan; Matsuri, Matsuri (Universitas Sebelas Maret, 2021)
This study aims to describe the critical thinking ability of students on Diversity Document in VA Purwotomo Public Primary School No. 97. Critical thinking is important to deal with the competition of life in the 21st century. This qualitative study uses qualitative descriptive and phenomenological approaches. This study recommends further studies on critical thinking skills. The teachers and students of Purwotomo Public Elementary School No. 97 Class VA, a total of 12 students, were the subjects of the study. The researcher used observations, interviews and documents to collect the data. The data analysis technique of this study is based on the interactive analysis technique of Miles and Huberman. Check the validity of the data using the triangulation method. Based on the results of the study, it can be concluded that students' critical thinking ability in diverse material in the civics classroom VA Purwotomo Public Elementary School No. Visibility is average level. This study needs to supplement the knowledge for teachers, schools and other researchers in developing critical thinking skills, especially in civics learning, so that they can optimize their knowledge. knowledge and practice in everyday life.